'Do Not Walk After Your Heart' (Num 15:39): Redescribing Moral Agency in Sirach and 4QInstruction - Kim, World (Revue de Qumran, 2022)
This article seeks to redescribe moral agency in Sirach and 4QInstruction by comparing how Sir 5:2 and 4Q417 1 i 27 allude to and re-use Num 15:39. Given that Num 15:39 is not a commonly utilized passage in Second Temple literature, Sirach and 4QInstruction share a 'distinctive feature' which allows for interesting comparison with respect to moral agency. Although scholars posit that moral agency is affirmed in Sirach while denied in 4QInstruction, recent studies invite further inquiry into whether these categories are apt to describe moral agency in either Sirach or 4QInstruction. This article shows that describing moral agency in Sirach and 4QInstruction is more complex than the binary 'voluntarism or determinism' might suggest and argues that these two workshave more in common with respect to moral agency than initially thought.